Fauna of tintinnids (Tintinnida, Ciliata) during an Arctic-Antarctic cruise, with the S/V “Croatian Tern” - Kršinić, Frano (Zootaxa, 2018)
An investigation of large tintinnids was carried out during the Arctic-Antarctic cruise aboard the S/V “Croatian Tern” in the period from 1994 to 1997. Samples were collected at 33 stations by vertical tows with a Nansen net with a 53 µm mesh size in the Mediterranean Sea, North Atlantic, Labrador Sea, Baffin Bay, the Beaufort, Chukchi and Bering Seas, East North Pacific, South Pacific, South East Pacific, Scotia Sea, and South West Atlantic. A total of 47 species of tintinnids were found, with the greatest diversity in the Tropical areas of the Pacific, Arctic and Subarctic. A very high total abundance was registered in the Bering Sea of 247,393 ind.m-3 and in the South-eastern Pacific of 66,211 ind.m-3. The dominant species in the northern areas was Ptychocylis obtusa and in the southern areas Eutintinnus rugosus.